Utilization of review form process or form 360 review employe performance in company using Configure Change Engine - Suhada, H.; Al Nasir, Aditiya Lityanian; Putra, Andhika Dwi (Pandawan Sejahtera Indonesia, 2020)
In building a company, which needs to be considered and very important is the accounting system, because to take a decision for the advancement of a company can use a rules-based system to configure products in the company. In today's modern era, the company's staff can access rules-based systems to configure products wherever and whenever they are connected to the Internet. This discovery provides the ability to test rules in system-based rules to configure the product. The configuration system defines the product component by using the elements contained in the catalog section and the rules that define the relationship between the product components. The user provides a test case that selects at least one section to include in the product configuration, and the configuration tester processes the rule to determine if at least one section is selected in case of a conflict test with the previous part of the plurality included in the product configuration.